A short history of human nutrition from prehistory to ancient civilisations - Lacasella, Giorgia Viola; Karaboue, Karidia (Progress in Nutrition, 2022)
The history of food is as long as the history of humanity: throughout history food, eating habits and behaviour have been conditioned by climatic, psychological, relational and technological factors since food can also be considered culture. Retracing the essential stages of human dietary evolution in ancient civilisations highlights how changing geographical location, climate and improving technologies have even changed (not always for the better) eating habits.